Correct performance of subcutaneous injections in plaque psoriasis: comparison of trained and untrained patients with different application systems in routine clinical care. (17th November 2021) - Stenger, Franziska; König, Anke; Ochsendorf, Falk; Kaufmann, Roland; Pinter, Andreas
Abstract: Background: Moderate-to-severe plaque psoriasis can be treated very successfully with systemic therapies. Often the therapeutics must be injected subcutaneously. This prospective observational study aimed to compare the correct preparation and performance of subcutaneous injections in trained and untrained patients with plaque psoriasis. Materials and Methods: We asked 110 patients (29.1% women, 70.9% men, injection system: 75.5% prefilled syringe, 24.5% autoinjector) to what extent they were trained for self-injection. While participants injected a sham injection with their current system, we evaluated the preparation, execution, and follow-up using a newly developed scoring system. Results: 87.3% ( n = 96) of the participants declared that they had been trained for self-injection. No statistically significant difference was observed between the trained and untrained participants in performing the injection correctly ( p = .458). The most common mistakes were the wrong preparation and follow-up of the injection. A bifactorial rank-variance analysis showed a negative influence of the factor injection system (prefilled syringe) on the total score ( p = .005). Conclusion: We can indicate that patients with plaque psoriasis are well prepared for subcutaneous self-injection. Self-injection of systemic therapies is easy to perform, especially with patient-friendly systems, and does not require specialized training.